Edu-Ecotourism Development Strategies Mapping - Taufiq Kurniawan; Riadatus Solihin; Widya Ananda Putri (Departement of Mathematics Education, 2023)
This study aims to find alternative strategies in developing the potential of Edu-ecotourism in Batudulang Village, Sumbawa Regency. This research begins by identifying the existing potency and analyzing the supporting and inhibiting factors, as well as identifying the opportunities that exist by using the SOAR analysis technique. This research employs descriptive qualitative. Data collection techniques used are field observations, interviews, and documentation. Determination of informants was also obtained by purposive sampling technique. The strategy from the results of this analysis is to develop all potencies that exists, both of natural resources such as biodiversity (flora and fauna) and the beauty of the landscape, as well as of the natural topography of the earth and the culture around the community that can be utilized. The Edu-ecotourism development strategy in Batudulang Village, Batulanteh District, Sumbawa Regency will be further discussed.